2020
DOI: 10.1177/1744806920903515
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of sensory transient receptor potential channels in response to the bioactive lipid sphingosine-1-phosphate

Abstract: Somatosensation encompasses a wide range of sensations including pain, itch, touch, and temperature and is essential for the detection of environmental stimuli, ultimately allowing an organism to escape, communicate, and adapt to its environment. Such sensations are detected by primary sensory neurons whose nerve endings are located in the skin. Compared to external stimuli, mechanisms underlying endogenous stimulation of primary sensory neurons, such as by lipids, are still largely unknown. Here, we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…In TRPA1 -/ TRPV1 + neurons, S1P trigger S1PR3-Gαq signaling, leading to phospholipase C (PLC) phosphorylation and activation of TRPV1 receptors (Figure 3) [61]. A recent study, even if mostly in accordance with the earlier-mentioned results, reported a major involvement of TRPV1 over TRPA1 in S1P-mediated pain and itch [62].…”
Section: Trends Trends In In Pharmacological Pharmacological Sciencessupporting
confidence: 79%
“…In TRPA1 -/ TRPV1 + neurons, S1P trigger S1PR3-Gαq signaling, leading to phospholipase C (PLC) phosphorylation and activation of TRPV1 receptors (Figure 3) [61]. A recent study, even if mostly in accordance with the earlier-mentioned results, reported a major involvement of TRPV1 over TRPA1 in S1P-mediated pain and itch [62].…”
Section: Trends Trends In In Pharmacological Pharmacological Sciencessupporting
confidence: 79%
“…Kittaka et al have demonstrated a potential link between TRPA1 and S1PR (27). S1P-induced responses in the dorsal root ganglia neurons in mice were partially inhibited by TRPA1 antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the subject, which was published in 2020 by Kittaka et al 44 . also showed significant downstream involvement of the two transient receptor potential channels in S1P signalling‐mediated pain and itch, making them an interesting topic for future research.…”
Section: S1p In Itch and Painmentioning
confidence: 99%
“…Further experiments such as Ca 2+ imaging and knockout animal models for TRPA1 and TRPV1, showed that the sensations were mediated through S1PR3 to TRPA1 and TRPV1, with TRPV1 being responsible for acute pain and heat hypersensitivity and TRPA1 mediating itch. 38 Another study on the subject, which was published in 2020 by Kittaka et al 44 also showed significant downstream involvement of the two transient receptor potential channels in S1P signalling-mediated pain and itch, making them an interesting topic for future research.…”
Section: S1p In Itch and Painmentioning
confidence: 99%